The Analysis of Government Support on The Implementation of Community-based Total Sanitation Programs in Sabu Raijua District - Three Hamdani; Marylin Susanti Junias; Dominirsep Ovidius Dodo (Lontar : Journal of Community Health, 2021)
There was an increase of diarrhea as many as 145,031 cases in East Nusa Tenggara, specifically in Sabu Raijua regency there were 2,070 cases. The government’s efforts to reduce diarrhea cases by the community-based total sanitation program. This study aims to analyze local government support in implementing the CBTS program in Sabu Raijua Regency for the period 2017-2019. This is a qualitative study with a descriptive approach. In the enabling environment for local government support related to policies based on the minister of health regulation number 3 in 2014 concerning CBTS and instruction from the Regent of Sabu Raijua Number 050/189/BAP-SR/IX/2014, for human resources, is still lacking and for the budget sourced from the National and Regional Expenditure Budget. Demand creation for the CBTS portion has been carried out to the RT/RW levels, and triggering have been carried out in all hamlets. In supply improvement technology, latrine sanitation facilities are available which are sold by entrepreneurs at affordable prices, to increase the capacity of sanitation market players, the government collaborates with NGOs to provide training on latrine construction, and the entrepreneurial sanitation market network is still having difficulty expanding the market. There is local government support in the form of Regent’s instruction, budget support, promotion, triggering, and availability of latrine at affordable prices as well as training for entrepreneurs in collaboration with NGOs, while this program has experienced constraints on the availability of human resources and difficulty in expanding the market.